(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
This paper examines the patriarchal society and the influence on gender discrimination and preference of males in India. It assumed a descriptive and analytical research design with the secondary data based on national surveys and census reports and government publications. The discussion was based on main scales of development which included trends on sex ratio, socio-cultural predictors, economic, and regional differences. The results showed that despite the slow movement of gender indicators over the recent years, the family decision-making, allocation of the resources, and attitudes toward social factors were still shaped by the patriarchal norms. Socio-cultural customs like dowry, patrilineality and conventional gender roles, and economic conditions like wage gap and low female labour contribution were some of the main causes of gender biases. Regional differences in gender outcomes and the disproportionate success of the interventions of the policy were also mentioned in the study. All in all, the study highlighted that patriarchal systems are still entrenched in the society and they still dictate gender relations despite the development work being done.